2011
DOI: 10.1590/s1806-66902011000200039
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de linhagens de feijão-de-vagem para as regiões Norte e Noroeste Fluminense

Abstract: Resumo -O feijão-de-vagem é uma hortaliça rica em fibras, proteínas e vitaminas. Dentro do programa de melhoramento do feijão-de-vagem da Universidade Estadual do Norte Fluminense Darcy Ribeiro (UENF), foram realizadas seleções nas populações F 2 , em campo; avançando até F 5 pelo método SSD, em casa de vegetação; selecionando 30 linhas promissoras em F 6 . Continuando o programa, a geração F 7 foi cultivada e avaliada, em campo, em Campos dos Goytacazes e em Bom Jesus do Itabapoana. As características avaliad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…By the estimates of the GCA effects on the PW, SWPP, and NSPP traits, it can be confirmed that the L1 Progenitor 19 (UENF 1445) and L3 (Top Seed Blue Line) genitors showed high and positive estimates, which suggests a possible contribution to the increase of these traits (Table 5). Similar results for pod weight and number of seeds per plants were found by Rainey and Griffiths (2005) and Francelino et al (2011). With regard to PL, the L10 (UENF 7-10-1) and L11 (UENF 7-12-1) genitors were the ones that presented positive values for GCA, which allows their indication in crosses to promote gains for that trait.…”
Section: Sources Of Variation Dfsupporting
confidence: 77%
“…By the estimates of the GCA effects on the PW, SWPP, and NSPP traits, it can be confirmed that the L1 Progenitor 19 (UENF 1445) and L3 (Top Seed Blue Line) genitors showed high and positive estimates, which suggests a possible contribution to the increase of these traits (Table 5). Similar results for pod weight and number of seeds per plants were found by Rainey and Griffiths (2005) and Francelino et al (2011). With regard to PL, the L10 (UENF 7-10-1) and L11 (UENF 7-12-1) genitors were the ones that presented positive values for GCA, which allows their indication in crosses to promote gains for that trait.…”
Section: Sources Of Variation Dfsupporting
confidence: 77%
“…Rio de Janeiro State is one of the largest national markets of snap beans and is responsible for 21% of the total produced in the Southeast of the country. However, despite being valued, this culture presents low productivity in the North and Northwest of the state due to its lack of cultivars adapted to these regions (Vilela et al;2009;Francelino et al, 2011). It is possible to obtain superior and adapted genotypes by means of genetic breeding techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These have contributed to the expansion of snap beans crop in several regions of Brazil, with it standing out as a good low operational cost option for Fall/ Winter in irrigated areas, since they enable the mechanization of most cultivation operations. Moreover, these cultivars produce good quality pods, which in turn has led to the greater demand for this group by producers (Francelino et al, 2011;Andrade et al, 2017;Peixoto & Cardoso, 2016;Vaz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%